The Extent of private Syrian Bank's Compliance with Audit Principals (A Fieldwork Study in Syria) (Latakia University Journal - Economic and Legal Sciences Series, 2022)
This study aims to verify the extent of Syrian private banks ’commitment to implementing generally accepted internal auditing standards. Whereas, the absence of the internal audit role will negatively affect these banks and will have disastrous effects, as happened with many international banks, such as: (Société Générale Bank, Baring bank Union Bank of Switzerland, and others). The study relied on using the descriptive approach in order to describe the current status of the studied banks with regard to the extent of their application of these standards. Therefore, the study surveyed the opinions of a sample of managers and employees of the internal audit department in a number of Syrian private banks, who expressed their views regarding the extent of obstacles to the application of internal auditing standards and regarding the extent to which their banks apply internal auditing standards related to: (1- The characteristics of the internal auditor, which consist of Standards related to goals, authorities, and responsibilities, standards related to independence and objectivity, standards related to necessary professional skills and care, and standards related to the quality assurance and improvement program. 2- Performance of the internal auditor.The hypotheses were tested using the T-test, and the results showed that Syrian private banks adhere to all recognized internal auditing standards, except for those related to quality assurance and improvement program.